2021
DOI: 10.3390/biom11101429
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Induces Accelerated Cell Aging in Murine Endothelium

Abstract: Bisphenol A (BPA) is a widespread endocrine disruptor affecting many organs and systems. Previous work in our laboratory demonstrated that BPA could induce death due to necroptosis in murine aortic endothelial cells (MAECs). This work aims to evaluate the possible involvement of BPA-induced senescence mechanisms in endothelial cells. The β-Gal assays showed interesting differences in cell senescence at relatively low doses (100 nM and 5 µM). Western blots confirmed that proteins involved in senescence mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 79 publications
(107 reference statements)
0
10
0
Order By: Relevance
“…N-acetylcysteine and genistein have been reported to play a protective role in cellular senescence ( 53 , 54 ). Bisphenol A, bleomycin, cisplatin and dexamethasone have been reported to induce cell senescence under some special circumstances ( 55 58 ). Moreover, conventional drugs that improve cardiac function after AMI such as the calcium sensitizer levosimendan and the angiotensin II-receptor blocker losartan have been found to reduce the expression of markers of senescence in heart tissue ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…N-acetylcysteine and genistein have been reported to play a protective role in cellular senescence ( 53 , 54 ). Bisphenol A, bleomycin, cisplatin and dexamethasone have been reported to induce cell senescence under some special circumstances ( 55 58 ). Moreover, conventional drugs that improve cardiac function after AMI such as the calcium sensitizer levosimendan and the angiotensin II-receptor blocker losartan have been found to reduce the expression of markers of senescence in heart tissue ( 52 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that BPA exposure can cause arterial endothelial dysfunction, uterine growth restriction, and impaired fetal placental development in rats (Barberio et al, 2021). It also induces the activation of unfolded protein response and cellular senescence through oxidative stress, induces programmed necrosis of mouse aortic endothelial cells and promotes the occurrence of cardiovascular disease (Moreno‐Gómez‐Toledano et al, 2021). Exposure to BPA in healthy or malnourished mice leads to left ventricular diastolic dysfunction, fibrosis, and coronary remodeling (García‐Arévalo et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Both its production and recycling involve the release of pollutants, xenobiotic compounds that should not be found in the air, rivers, or the human population[ 1 , 2 ]. One of the most important, due to its wide distribution and variety of biological effects, is bisphenol A (BPA)[ 3 - 6 ]. The European Chemicals Agency has recently included BPA within the Candidate List of substances of very high concern due to its properties as an endocrine disruptor and its potentially harmful effect on reproduction[ 7 ].…”
Section: Introductionmentioning
confidence: 99%